A gastro-intestinal soluble coating material, its preparation method and use

By constructing a two-phase structure consisting of a continuous phase of hydrogenated oil and a dispersed phase of shellac-coated biodegradable microspheres, the problem of incomplete disintegration of the coating membrane in the intestine was solved, achieving complete fragmentation of the shell membrane and high-temperature stability, thus improving the application effect of polyphenolic substances.

CN122623770APending Publication Date: 2026-08-25HUBEI RUNFAN BIOTECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611021976.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-08-25

AI Technical Summary

Technical Problem

In existing technologies, the coating membrane does not completely disintegrate in the intestine, resulting in shell membrane residue, which affects animal health and product efficacy. Furthermore, polyphenols are easily oxidized and deactivated at high temperatures.

Method used

The gastrointestinal coating material employs a biphase structure, comprising a continuous phase of hydrogenated oil and a dispersed phase of shellac-coated biodegradable microspheres. The microspheres degrade in the intestinal environment to form through channels, achieving orderly disintegration of the coating membrane and avoiding shell membrane residue.

Benefits of technology

It achieves complete disintegration of the coating membrane in the intestine, reduces membrane residue, maintains high-temperature stability and gastric protection performance, and improves the application effect and user acceptance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a kind of over gastrointestinal coating materials and preparation method and application thereof, belong to functional coating material and feed additive preparation technical field.The coating material has continuous phase-dispersed phase two-phase structure: continuous phase includes hydrogenated oil, as over stomach barrier and heat-resistant framework;Dispersed phase includes the degradable microsphere with shellac coating on surface, uniformly embedded in continuous phase.Shellac coating has the dual function of protecting anchoring in stomach and dissolving and exposing microsphere in intestinal pH response.After microsphere degrades in intestinal, form spherical cavity in continuous phase in situ and interconnect into through channel network, guide coating film to be fragmented into small fragments along the arrangement direction of microsphere, it is expected to solve the shell film residue problem caused by the disordered dissolution of existing single-phase homogeneous film depending on surfactant.Microsphere and microfibrillated cellulose can form a synergistic framework to enhance the stability of high-temperature form.The coating material simultaneously realizes the organic unity of high-temperature resistance, over stomach protection and intestinal disintegration, and is suitable for coating treatment of tannic acid and other plant polyphenols feed additives.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional coating materials and feed additive preparation technology, specifically relating to a gastrointestinal coating material suitable for coating plant polyphenolic active ingredients, its preparation method and application. Background Technology

[0002] In livestock and poultry farming, plant polyphenols such as tannins and tea polyphenols have antibacterial, anti-diarrheal, and gut health-promoting effects, and can be used as alternatives to antibiotics and zinc oxide in feed additives. However, direct feeding of these polyphenols presents two problems: First, polyphenols can bind with proteins in feed and gastrointestinal mucosal proteins to form insoluble complexes, which not only reduce their own efficacy but also damage intestinal morphology and affect the animal's digestion and absorption of nutrients. Second, feed processing usually requires high-temperature pelleting at 80-90℃, and polyphenols have poor thermal stability, making them prone to oxidation and inactivation when directly exposed to high temperatures.

[0003] To overcome the above problems, existing technologies use hydrogenated oils, polyacrylic acid resins, surfactants, and thickeners to construct a coating film for gastric encapsulation of active ingredients. The principle is as follows: hydrogenated oils are protected from decomposition by lipases in the stomach, and upon entering the intestines, they are released through lipase hydrolysis and surfactant-guided disintegration.

[0004] However, during the research process, the applicant of this invention discovered that the coating film of the prior art leaves a visible, undigested shell-like substance after simulated intestinal digestion. Further analysis confirmed that the root cause lies in the fact that the coating film has a single-phase homogeneous structure, and its disintegration mechanism relies on the disordered emulsification effect of surfactants—surfactants guide the gradual dissolution of lipids in the intestine, but the irregular dissolution front and uncontrollable disintegration process prevent the coating film from completely disintegrating, ultimately leaving behind relatively large shell fragments. This shell residue not only wastes coating material but may also place an additional burden on the animal's intestines, affecting the actual application effect of the product and user acceptance. Currently, no prior art recognizes that this shell residue is a technical problem that needs to be solved, nor has any technical solution been provided.

[0005] Therefore, there is an urgent need for a coating material that can maintain excellent gastric protection and high-temperature resistance, while also achieving complete disintegration in the intestine and reducing or eliminating shell membrane residue. Summary of the Invention

[0006] In view of this, the present invention proposes a gastrointestinal coated material, which aims to solve the technical problems of incomplete disintegration of the coating membrane and residual shell membrane in the intestine in the prior art.

[0007] The technical solution of this invention is achieved as follows: This invention provides a gastrointestinal coated material having a continuous-phase-dispersed-phase biphase structure. This biphase structure is the core concept of this invention: the continuous phase acts as the framework and barrier of the coating membrane, undertaking the basic functions of gastric protection and heat-resistant molding; the dispersed phase acts as the structural template for disintegration, undertaking the function of guiding the coating membrane to break down in a predetermined manner. Functionally, the two phases are independent yet synergistic, and temporally sequential: in the stomach, the continuous phase provides complete protection while the dispersed phase remains stable and latent; in the intestine, the dispersed phase triggers first, followed by the disintegration of the continuous phase.

[0008] Compared with the existing technology where single-phase homogeneous membranes rely on surfactants for disordered emulsification and dissolution, the two-phase structure of this invention separates the "disintegration" function from the continuous phase and entrusts it to the dispersed phase for dedicated execution, which is expected to achieve a leap from disorder to order in the disintegration process.

[0009] In some embodiments, the continuous phase comprises hydrogenated oils. Hydrogenated oils are solid at room temperature with a melting point of 55-85°C. They remain intact and undigested in the gastric environment (pH 1-4, lacking lipase), and maintain their solid state without softening or deforming under high-temperature granulation conditions (80-90°C), thus serving as both a gastric protective barrier and a heat-resistant structural framework. The hydrogenated oils can be selected from at least one of hydrogenated palm oil, hydrogenated rapeseed oil, hydrogenated soybean oil, hydrogenated castor oil, or palm stearin. Hydrogenated castor oil, in particular, has a melting point exceeding 85°C and maintains morphological stability even under more demanding granulation temperature conditions, making it suitable for high-temperature granulation processes.

[0010] In some embodiments, the dispersed phase comprises biodegradable microspheres uniformly embedded in the continuous phase. The biodegradable microspheres are the key functional unit for achieving disintegration-induced pores in this invention, playing multiple roles in the system: First, the microspheres themselves possess a rigid structure and high thermal stability, remaining unmelted and undeformed at the high temperatures of granulation, potentially enhancing the morphological stability of the continuous phase at high temperatures as rigid fillers; second, the microspheres do not degrade or dissolve in the gastric acid environment, remaining completely encapsulated by the continuous phase without exposure, thus not adversely affecting the gastric protection function; third, the microspheres degrade or dissolve in the intestinal environment, leaving spherical cavities in situ. After degradation, the cavities of adjacent microspheres interconnect, forming a channel network penetrating the coating membrane. Digestive fluids and lipases penetrate the membrane along these channels, achieving simultaneous dissolution over a large area. The coating membrane fragments into tiny fragments along the microsphere alignment direction, potentially fundamentally reducing or eliminating intact membrane residues.

[0011] In some embodiments, the biodegradable microspheres are at least one of cross-linked starch microspheres, chitosan microspheres, pectin microspheres, or calcium alginate microspheres. Cross-linked starch microspheres are a preferred option: starch raw materials are widely available, inexpensive, and meet food-grade compliance requirements; after cross-linking treatment, the thermal decomposition temperature of the microspheres exceeds 200°C, and they remain completely rigid at granulation temperature; cross-linked starch microspheres remain stable in the gastric environment due to the lack of amylase, but are degraded by pancreatic amylase in the intestinal environment, exhibiting good gastrointestinal environment response differences.

[0012] In some embodiments, the biodegradable microspheres have a particle size of 30-80 μm. The selection of the microsphere particle size is based on the following considerations: if the particle size is too small (less than 20 μm), the cavity formed after degradation will be difficult to form an effective through channel, and the dispersion of the microspheres in the coating solution will be more difficult; if the particle size is too large (more than 100 μm), each microsphere occupies too much space, which may lead to partial exposure of the microspheres when the coating film thickness is limited, weakening the gastric protection effect. The particle size range of 30-80 μm can balance the cavity penetration effect and the integrity of the coating film.

[0013] In some embodiments, the amount of biodegradable microspheres added is such that their volume fraction in the continuous phase exceeds the percolation threshold. Percolation theory indicates that when the volume fraction of the filling phase in the continuous phase exceeds approximately 16 vol%, the connectivity probability between adjacent particles increases significantly, forming a continuous network throughout the material. This invention utilizes this principle, controlling the amount of microspheres added to ensure that their volume fraction exceeds the percolation threshold, which facilitates the interconnection of cavities formed after microsphere degradation, creating a network of interconnected channels. When the amount of microspheres added is below the percolation threshold, the cavities tend to be isolated after degradation, failing to form continuous channels, and the disintegration effect may significantly decrease. Therefore, the percolation threshold can serve as an objective reference for determining the lower limit of the effective amount of microspheres added.

[0014] In some embodiments, the surface of the biodegradable microspheres has a shellac coating comprising shellac and a cross-linking structure-forming agent. Shellac (also known as lac) is a natural resin with a well-defined pH-responsive solubility characteristic: it is insoluble in environments below pH 6.8 and dissolves rapidly at pH 6.8 or above. This invention applies shellac to the surface coating of microspheres, potentially achieving two sequential functions: In the first stage (in the stomach, low pH), the shellac coating completely encapsulates the microsphere surface, protecting the microspheres from contact with gastric juices. Simultaneously, the inventors hypothesize that the cross-linking structure-forming agent coordinates with or interacts with the carboxyl groups in the shellac molecules, consuming some free hydrophilic groups, which may enhance the hydrophobicity of the coating surface. This facilitates stable dispersion and interfacial bonding of the microspheres in the hydrogenated oil continuous phase, reducing the risk of microsphere detachment during granulation and gastric peristalsis. In the second stage (mid-to-late intestinal tract, pH ≥ 6.8), the shellac coating dissolves rapidly, cleanly exposing the microsphere surface, allowing the microspheres to be promptly recognized and degraded by intestinal amylases. After degradation, the microspheres form cavities in situ, creating localized stress concentrations within the coating membrane. Digestive fluids seep into these cavities, forming an internal dissolution front that may preferentially guide the coating membrane to break down along the microsphere alignment. Upon dissolution of the shellac coating, the cross-linked structures simultaneously disintegrate, ensuring that the degradation process on the microsphere surface is unaffected by these cross-linked structures. These two functions unfold sequentially in time and do not interfere with each other spatially, potentially achieving a switching effect between "protection and anchoring" in the stomach and "exposure and triggering" in the intestine.

[0015] In some embodiments, the crosslinking structure forming agent is selected from at least one of calcium salts, wax microparticles, and fatty acids. The role of the crosslinking structure forming agent may be to construct crosslinked networks or hydrophobic anchors in the shellac coating, thereby enhancing the interfacial bonding between the shellac coating and the hydrogenated oil continuous phase. Specifically: calcium salts (such as calcium carbonate and calcium lactate) form micro-crosslinked networks by coordinating with carboxyl groups in shellac molecules, consuming some free hydrophilic groups, which may enhance the hydrophobicity of the coating surface; wax microparticles (such as rice bran wax microparticles, with a particle size of 1-5 μm and a melting point greater than 78°C) are semi-embedded in the shellac coating during film formation, and the exposed wax portion has material similarity to the hydrogenated oil, which may form physical anchors; fatty acids (such as stearic acid) introduce hydrophobic side chains through esterification with hydroxyl groups in shellac molecules, which may cause the coating to spontaneously align at the microsphere-continuous phase interface. The above crosslinked structures disintegrate simultaneously when the shellac coating dissolves, without forming additional residues.

[0016] In some embodiments, the shellac coating comprises 8-15% of the biodegradable microspheres by mass, wherein shellac accounts for 5-10% and the cross-linking structure forming agent accounts for 3-5%. This dosage range takes into account the balance between the protective effect of the coating and the degradation efficiency of the microspheres: if the coating is too thin (less than 5%), it may be difficult to form a complete protective layer; if the coating is too thick (more than 15%), the dissolution time of shellac in the intestine may be prolonged, or the degradation efficiency of the microspheres may be affected.

[0017] In some embodiments, the coating material further comprises microfibrillated cellulose (MFC). MFC may play multiple roles in the system: First, MFC forms a three-dimensional physical network in the coating solution, supporting the biodegradable microspheres and keeping them in a monodisperse suspension state, preventing sedimentation and aggregation. This is beneficial for the microspheres to maintain a uniform spatial arrangement during subsequent film formation, which is an important prerequisite for achieving uniform pore formation. Second, MFC fibers have a high aspect ratio and rigidity, and can form a physical network in the continuous phase after drying. It is speculated that the skeletal structure formed by this network and the rigid microspheres may help maintain the morphological integrity of the membrane when the hydrogenated oil tends to soften, reducing the risk of membrane collapse or adhesion at the high temperature of granulation. Third, MFC fibers may tend to align along the membrane plane during the emulsification and spraying of the coating solution. After the microspheres degrade and form cavities, the fiber-matrix interface, as a natural weak interface in the material, may become a preferential path for the digestive solution to penetrate and expand, thereby helping to guide the coating membrane to break up along the microsphere alignment direction.

[0018] In some embodiments, the coating material is surfactant-free, or the surfactant content does not exceed 2% of the total mass of the coating material. Prior art teaches that surfactants are crucial for the emulsification and stabilization of oil-based coating solutions and for intestinal pore formation. However, analysis has shown that when biodegradable microspheres are introduced as pore-forming templates, retaining conventional amounts of surfactant may lead to the formation of an interfacial film on the microsphere surface due to emulsification. This interfacial film may, to some extent, hinder the exposure and degradation of the microspheres after shellac dissolution, adversely affecting the disintegration process. Therefore, this invention chooses to significantly reduce or even completely eliminate surfactants, allowing microsphere exposure and triggering to be entirely achieved through the dissolution of the shellac coating in the intestinal pH environment, thereby avoiding potential interference with microsphere function by surfactants.

[0019] In some embodiments, the coating material is used to coat plant polyphenolic active ingredients. Plant polyphenolic active ingredients include tannins, tea polyphenols, grape seed extract, etc. These ingredients share common characteristics: they need to function in the intestines, they bind to proteins when directly fed, and they need to withstand the high temperatures of feed pelleting. The coating material of the present invention is specifically designed to address the specific needs of these ingredients.

[0020] In some embodiments, the active plant polyphenolic ingredient is tannic acid. Tannic acid is added in large quantities to feed, has a prominent need for gastric protection, and requires high tolerance to high temperatures during pelleting. Furthermore, the problem of shell membrane residue in existing coated products is most pronounced with tannic acid, making it a preferred application of this invention.

[0021] The present invention has the following advantages over the prior art. The enteric-coated coating material of this invention, by constructing a two-phase structure of a continuous hydrogenated oil phase and a shellac-coated biodegradable microsphere dispersion phase, transforms the disintegration mechanism of the coating membrane from disordered dissolution dependent on surfactants to fragmentation based on microsphere degradation. This is expected to solve the problems of incomplete intestinal disintegration and residual intact shell membranes in existing coating membranes, achieving the technical effect of miniaturized disintegration fragments. Simultaneously, the rigidity and high thermal stability of the microspheres themselves, together with the microfibrillated cellulose nanofiber network, may form a synergistic scaffold support, making the morphological stability and barrier integrity of the coating material under high-temperature granulation conditions superior to existing solutions that rely solely on the melting point of hydrogenated oils. This is expected to achieve an organic unity of the three core properties: high-temperature resistance, gastric protection, and intestinal disintegration. In addition, the shellac coating has the dual functions of a microsphere protective layer and a release trigger switch. It provides protection and anchoring in the stomach and dissolves and exposes the microspheres in the intestine. The two functions are sequential and do not conflict with each other, which is expected to achieve the trigger release of microspheres at the target site. Furthermore, the reverse deletion of surfactants not only does not weaken the process applicability of the coating liquid, but may also avoid the interference of surfactants on microsphere exposure, further improving the intestinal release efficiency. Detailed Implementation

[0022] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0023] In the following examples and comparative examples, all raw materials used were commercially available conventional products. The determination of tannic acid content was performed according to NYSL-1006-2022. Simulated gastric and intestinal fluids were prepared according to pharmacopoeia methods. Unless otherwise specified, all percentages below are by mass.

[0024] Preparation Example 1: Preparation of Tannic Acid Particles Weigh out tannic acid (dark red or brown granules, odorless, with a slightly peculiar odor, extremely astringent taste, soluble in water and ethanol, readily soluble in glycerol, almost insoluble in ether and chloroform, molecular formula C). 76 H 52 O 4670 kg of corn starch and 30 kg of binder (composed of 80 wt% corn starch, 10 wt% microcrystalline cellulose and 10 wt% talc) were added to the hopper of an HWMG200 high-efficiency wet mixing granulator and mixed evenly. The material was extruded using a low-temperature extruder at 40 rpm and a 0.6 mm orifice, and then rolled into tannic acid granules at 300 rpm using a 700 mm diameter spheroidizer.

[0025] Preparation Example 2: Preparation of shellac-coated crosslinked starch microspheres Cross-linked starch microspheres (particle size 40-60 μm) are commercially available products, or can be prepared using sodium trimetaphosphate as a cross-linking agent according to known methods.

[0026] The cross-linked starch microspheres were immersed in an ethanol solution containing 10 wt% shellac and 0.3 wt% calcium carbonate, and stirred for 30 minutes to allow the shellac and calcium carbonate to be uniformly deposited on the surface of the microspheres. The ethanol solvent was removed by spray drying, forming a shellac coating with a calcium ion-coordinated cross-linked structure on the surface of the microspheres. The resulting shellac coating accounted for approximately 10% of the total mass of the microspheres, of which shellac accounted for approximately 8% and calcium carbonate accounted for approximately 2%.

[0027] Following the method described above, microspheres of different specifications were prepared respectively: Chitosan microspheres (particle size 30-50 μm) were used instead of cross-linked starch microspheres, and the rest of the preparation was the same as in this example, to obtain shellac-coated chitosan microspheres; By replacing cross-linked starch microspheres with pectin microspheres (particle size 50-70 μm), and otherwise following the same preparation example, shellac-coated pectin microspheres were obtained. The cross-linked starch microspheres were replaced with 20–40 μm and 60–80 μm respectively, and the rest were the same as in this preparation example, to obtain shellac-coated microspheres with different particle sizes; Rice bran wax microparticles (particle size 1-3 μm, accounting for 10% of the mass of shellac) were used to replace calcium carbonate, and the rest were the same as in this preparation example, to obtain wax microparticle-embedded shellac-coated microspheres; Stearic acid-grafted shellac (5% by weight of shellac) was used to replace ordinary shellac, without the addition of any crosslinking agent, and the rest of the preparation was the same as in the previous example, to obtain fatty acid-grafted shellac coated microspheres.

[0028] General coating solution preparation process Hydrogenated oil was heated to 65°C to melt and kept at that temperature for later use. Microfibrillated cellulose (MFC, diameter 20–100 nm, length several to tens of micrometers) was dispersed in hot water and stirred until homogeneous to form an MFC suspension. The shellac-coated microspheres obtained in Preparation Example 2 were added to the MFC suspension and stirred until homogeneous to form a suspension phase containing microspheres. The molten hydrogenated oil was mixed with the suspension phase containing microspheres and emulsified at 8000 r / min for 45 minutes at 65°C to obtain a coating solution. The coating solution was used under stirring at 65°C, and the time from preparation of the coating solution to completion of spraying was controlled within 4 hours.

[0029] General fluidized bed coating process The coating solution and the tannic acid particles obtained in Preparation Example 1 were simultaneously introduced into the coating fluidized bed. The inlet temperature was maintained at 55±5℃, the outlet temperature at 40℃, and the air velocity at 30-36 Hz. Coating was carried out for 2 hours. After discharge, the material was sieved, and the product that passed 100% through a 20-mesh sieve and less than 5% through an 80-mesh sieve was collected, which is the enteric-coated material.

[0030] Performance testing methods Simulated gastric juice dissolution rate test: 1g of each sample was added to 100mL of simulated gastric juice (pH 3.2, containing pepsin), and the mixture was placed in an incubator at 37℃ and 150r / min with shaking. Samples were taken at 30min, 60min, and 120min to determine the tannic acid content and calculate the dissolution rate. The experiment was repeated three times, and the average value was taken.

[0031] Simulated intestinal fluid release rate test: 1g of each sample was added to 100mL of simulated intestinal fluid (pH 6.8, containing pancreatic lipase and pancreatic amylase), and the mixture was placed in an incubator at 37℃ and 150r / min with shaking. Samples were collected at 1h, 2h, 4h, and 6h to determine the tannic acid content and calculate the release rate. The experiment was repeated three times, and the average value was taken.

[0032] Observation of shell membrane residue: 1g of sample was placed in 100mL of simulated intestinal fluid and digested at 37℃ and 150r / min for 6 hours. After digestion, the digest was poured into a petri dish with a black background and observed and recorded under natural light.

[0033] Heat resistance test: Weigh 1g of each sample and place them in 10mL of aqueous solution at 60℃, 70℃, 80℃ and 90℃ respectively. After standing for 5 minutes, stir for 10 seconds and measure the release rate of tannic acid in the aqueous solution to evaluate the resistance of the coating material in hot water at different temperatures.

[0034] Example 1 (Calcium cross-linked shellac coating + hydrogenated palm oil + MFC) The coating process is carried out according to the general coating solution preparation process and the general fluidized bed coating process, wherein: The hydrogenated oil uses hydrogenated palm oil (melting point 58-62℃), with a dosage of 1200g; The calcium-crosslinked shellac-coated crosslinked starch microspheres (particle size 40-60 μm) obtained in Preparation Example 2 were used in an amount of 120 g. MFC usage: 25g; Water usage: 1600g; The ratio of coating solution to tannic acid particles (Preparation Example 1) was 1:2.

[0035] Example 2 (Wax microparticle inlaid shellac coating) The calcium cross-linked shellac-coated microspheres in Example 1 were replaced with the wax microparticle-embedded shellac-coated microspheres (particle size 40-60 μm) obtained in Preparation Example 2, and the rest were the same as in Example 1.

[0036] Example 3 (Fatty acid grafted shellac coating) The calcium-crosslinked shellac-coated microspheres in Example 1 were replaced with fatty acid-grafted shellac-coated microspheres (particle size 40-60 μm) obtained in Preparation Example 2, and the rest were the same as in Example 1.

[0037] Example 4 (High Melting Point Hydrogenated Oils) The hydrogenated palm oil in Example 1 was replaced with hydrogenated castor oil (melting point 85°C), and the rest was the same as in Example 1.

[0038] Example 5 (microsphere size 20-40 μm) The microsphere size in Example 1 was replaced with 20–40 μm, and the rest was the same as in Example 1.

[0039] Example 6 (microspheres with a diameter of 60–80 μm) The microsphere size in Example 1 was replaced with 60-80 μm, and the rest was the same as in Example 1.

[0040] Example 7 (Chitosan Microspheres) The cross-linked starch microspheres in Example 1 were replaced with chitosan microspheres (particle size 30-50 μm, shellac coating as in Preparation Example 2), and the rest were the same as in Example 1.

[0041] Example 8 (Pectin Microspheres) The cross-linked starch microspheres in Example 1 were replaced with pectin microspheres (particle size 50-70 μm, shellac coating as in Preparation Example 2), and the rest were the same as in Example 1.

[0042] Example 9 (Different active ingredients – tea polyphenols) In Preparation Example 1, tannins were replaced with tea polyphenols, and the rest of the preparation was the same as in Preparation Example 1 to obtain tea polyphenol granules. The coating process was the same as in Example 1.

[0043] Example 10 (Different active ingredients – grape seed extract) In Preparation Example 1, tannic acid was replaced with grape seed extract, and the rest of the preparation was the same as in Preparation Example 1 to obtain grape seed extract granules. The coating process was the same as in Example 1.

[0044] Comparative Example 1 (without microspheres – refer to Example 1 of CN120345648A) Coated tannic acid was prepared according to the method described in Example 1 of CN120345648A.

[0045] (1) Preparation of coating solution: 100g of glyceryl succinate, 100g of sodium stearoyl lactylate, 100g of D-mannitol, 20g of hydroxypropyl starch and 100g of polyacrylic acid resin were added to 1600g of water and stirred until completely dissolved; 1200g of hydrogenated palm oil was added after heating and melting, and stirred for 10 minutes to disperse it evenly; then emulsified for 45 minutes to prepare the coating solution, and kept at 60-70℃ for later use.

[0046] (2) Fluidized bed coating: The coating liquid and 3800g of tannic acid particles obtained in Preparation Example 1 are simultaneously introduced into the coating fluidized bed. The inlet temperature is maintained at 55±5℃, the outlet temperature is below 40℃, and the air velocity is 30 Hz. The coating is carried out for 2 hours, and then the material is discharged and sieved to obtain a product in which 100% of the material passes through a 20-mesh sieve and less than 5% passes through an 80-mesh sieve.

[0047] Comparative Example 2 (without shellac coating) The shellac coating step in Example 1 was omitted, and cross-linked starch microspheres (particle size 40-60 μm) without any surface treatment were used directly, with the rest being the same as in Example 1.

[0048] Comparative Example 3 (No MFC, conventional thickener) The MFC in Example 1 was replaced with an equal amount of hydroxypropyl starch, and the rest was the same as in Example 1.

[0049] Comparative Example 4 (retaining the usual amount of surfactant) Based on the coating solution formulation of Example 1, polyglycerol fatty acid esters were added to bring the total amount to 150g, and the rest were the same as in Example 1.

[0050] Comparative Example 5 (microsphere addition amount below the percolation threshold) The amount of microspheres added in Example 1 was reduced from 120g to 50g (corresponding to a volume fraction of approximately 8 vol%, which is lower than the percolation threshold of approximately 16 vol% for spherical packing in a three-dimensional continuous phase), while the rest remained the same as in Example 1.

[0051] Performance test results 1. Simulated gastric juice dissolution rate test The tannic acid dissolution rates of each embodiment and comparative example at different time points in simulated gastric fluid are shown in Table 1.

[0052] Table 1. Results of dissolution rate test of simulated gastric juice (pH 3.2)

[0053] As shown in Table 1, the dissolution rates of all embodiments of the present invention in simulated gastric fluid were controlled below 10% (6.5%–9.1%) after 2 hours, significantly lower than those of Comparative Example 1 (45.8%) and Comparative Example 2 (34.2%). Comparative Example 2, lacking the protective shellac coating, may have experienced gastric fluid penetration along the microsphere-oil interface, leading to a significantly higher dissolution rate. The gastric fluid dissolution rates of Comparative Examples 3 and 4 were also significantly higher than those of Example 1 (22.6% and 28.5%, respectively), indicating that the MFC thixotropic suspension system and low surfactant strategy may help maintain the density of the coating film in the gastric environment. The dissolution rate of Comparative Example 5 (12.3%) was slightly higher than that of Example 1, suggesting that the amount of microspheres added may have a slight impact on the gastric acid barrier performance. In Example 4, the gastric fluid dissolution rate was further reduced to 6.5% after using high-melting-point hydrogenated castor oil, indicating that a continuous phase with a higher melting point may help enhance the gastric acid barrier effect.

[0054] 2. Simulated intestinal fluid release rate test Table 2 shows the tannic acid release rates at different time points in simulated intestinal fluid for each embodiment and comparative example.

[0055] Table 2 Results of release rate test of simulated intestinal fluid (pH 6.8)

[0056] As shown in Table 2, the release rates of all embodiments of the present invention in simulated intestinal fluid exceeded 90% after 4 hours and 96% after 6 hours, significantly higher than Comparative Example 1 (only 85.4% after 6 hours). This may be because the microspheres degrade in the intestine, forming cavities that interconnect, promoting the penetration of digestive fluid into the membrane and achieving simultaneous dissolution over a larger area. Although Comparative Example 2 had a high release rate (reaching 52.3% in 1 hour), this was due to the lack of a shellac coating delay, causing the microspheres to be exposed and degraded at the front of the intestine, making the release sites uncontrollable. The intestinal release rates of Comparative Examples 3 and 4 were significantly lower than those of Example 1, possibly reflecting the positive effects of the MFC fiber network and the low surfactant system on the disintegration process, respectively. The release rate of Comparative Example 5 was close to that of Comparative Example 1, indicating that when the amount of microspheres added is below the percolation threshold, the degradation cavities may tend to be isolated and unable to form continuous through channels, significantly weakening the disintegration effect. Examples 5 and 6 showed a clear trend of increasing release rate with increasing microsphere particle size, indicating that the release rate can be controlled by adjusting the microsphere particle size.

[0057] 3. Observation of shell membrane residue The results of the observation of shell membrane residue after 6 hours of digestion in simulated intestinal fluid for each embodiment and comparative example are shown in Table 3.

[0058] Table 3. Observation results of shell membrane residue after 6 hours of simulated intestinal fluid digestion.

[0059] As can be seen from the observations in Table 3, none of the embodiments of the present invention had intact shell membranes after digestion, leaving only tiny fragments indistinguishable to the naked eye, indicating that the coating membrane achieved relatively thorough fragmentation in the intestine. In contrast, Comparative Example 1 left behind clearly intact shell membrane-like material after digestion, which could be completely picked out, directly confirming the shell membrane residue problem caused by the disordered dissolution of existing single-phase homogeneous membranes by surfactants. Comparative Examples 3 and 4 still had discernible flakes, indicating that MFC and the low-surfactant system play an important role in achieving complete fragmentation of the coating membrane. Comparative Example 5 left behind larger shell membrane fragments, similar to Comparative Example 1, further indicating that when the amount of microspheres added is below the percolation threshold, it may not effectively promote disintegration. These results directly demonstrate from a macroscopic perspective that the "continuous phase-dispersed phase" two-phase structure design of the present invention has a positive effect on reducing shell membrane residue.

[0060] 4. Heat resistance test The 5-minute release rates of each embodiment and comparative example in hot water at different temperatures are shown in Table 4.

[0061] Table 4. Results of 5-minute release rate test of hot water at different temperatures.

[0062] As shown in Table 4, the release rates of all embodiments of the present invention at various temperatures are significantly lower than those of Comparative Example 1, indicating superior heat resistance. Example 1 showed a release rate of only 5.8% at 80°C and only 8.6% at 90°C, far lower than Comparative Example 1 (9.2% at 80°C and 14.5% at 90°C). Comparing Example 1 with Comparative Example 3 (without MFC, 16.8% at 90°C) suggests that the framework structure formed by MFC and microspheres may have a positive effect on the morphological stability of the membrane at high temperatures—when the hydrogenated oil tends to soften, this framework structure may help maintain the membrane's morphology and reduce the risk of rupture at high temperatures. Example 4, using high-melting-point hydrogenated castor oil, showed a release rate of only 6.8% at 90°C, further improving heat resistance, indicating that selecting hydrogenated oils with higher melting points can meet more demanding high-temperature granulation requirements. Comparative Example 4 showed the worst heat resistance (17.2% at 90°C), indicating that the presence of surfactants may reduce the membrane's density and morphological stability at high temperatures.

[0063] 5. Applicability verification of different active ingredients The performance test results of the coated products obtained in Example 9 (tea polyphenols) and Example 10 (grape seed extract) are shown in Table 5.

[0064] Table 5 Performance test results of products coated with different active ingredients

[0065] As shown in Table 5, after replacing the active ingredient tannic acid with tea polyphenols or grape seed extract, the resulting coated products exhibited dissolution rates of less than 30% in simulated gastric fluid after 2 hours and release rates exceeding 96% in simulated intestinal fluid after 6 hours, with no intact shell membrane residue after digestion. This indicates that the enteric coating material of the present invention has good applicability to plant polyphenolic active ingredients, and the pH-responsive dissolution characteristics of the shellac coating and the pore-forming mechanism of the microspheres are independent of the type of specific active ingredient.

[0066] Based on the performance test results of the above embodiments and comparative examples, the enteric coating material of the present invention achieves a unified balance of three core properties—high temperature resistance, gastric protection, and intestinal disintegration—by constructing a two-phase structure of "hydrogenated oil continuous phase + shellac-coated biodegradable microsphere dispersion phase." Compared with existing single-phase homogeneous membranes, it exhibits superior gastric juice barrier performance, faster and more thorough intestinal release rate, reduced shell membrane residue, and significantly enhanced heat resistance. This synergistic improvement in various properties is unpredictable in existing technologies.

[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A gastrointestinal coated material, characterized in that, It has a continuous-dispersed two-phase structure: The continuous phase comprises hydrogenated oils; The dispersed phase comprises biodegradable microspheres uniformly embedded in the continuous phase, which remain stable in the gastric environment and degrade in the intestinal environment to form cavities in the continuous phase and guide the orderly disintegration of the coating material; The surface of the biodegradable microspheres has a shellac coating comprising shellac and a cross-linking structure forming agent. The shellac coating is used to protect the biodegradable microspheres in a gastric environment and to dissolve in response to pH changes in an intestinal environment to expose the biodegradable microspheres.

2. The enteric-coated material according to claim 1, characterized in that, The biodegradable microspheres are at least one of cross-linked starch microspheres, chitosan microspheres, pectin microspheres, or calcium alginate microspheres.

3. The enteric-coated material according to claim 2, characterized in that, The biodegradable microspheres have a particle size of 30-80 μm.

4. The enteric-coated material according to claim 1, characterized in that, The cross-linking structure forming agent is selected from at least one of calcium salts, wax microparticles, and fatty acids; the shellac coating accounts for 8-15% of the mass of the biodegradable microspheres.

5. The enteric-coated material according to claim 1, characterized in that, It also contains microfibrillated cellulose, which is dispersed in the continuous phase and together with the biodegradable microspheres forms a skeletal network.

6. The enteric-coated material according to claim 1, characterized in that, The volume fraction of the biodegradable microspheres in the continuous phase is greater than 16 vol.

7. The enteric-coated material according to claim 1, characterized in that, The coating material contains no surfactant, or the surfactant content does not exceed 2% of the total mass of the coating material.

8. A method for preparing a gastrointestinal coated material according to any one of claims 1 to 7, characterized in that, Includes the following steps: (1) The biodegradable microspheres are surface coated with the shellac and the cross-linking structure forming agent to obtain biodegradable microspheres with shellac coating; (2) Heat and melt the hydrogenated oil; disperse the biodegradable microspheres with shellac coating obtained in step (1) and microfibrillated cellulose in water to form a suspension; The molten hydrogenated oil is mixed with the suspension and emulsified to obtain a coating solution; (3) The coating solution and active ingredient particles are coated in a fluidized bed to obtain the enteric coated material.

9. The preparation method according to claim 8, characterized in that, In step (3), the active ingredient particles are at least one of tannic acid particles, tea polyphenol particles, or grape seed extract particles.

10. The use of the enteric-coated material according to any one of claims 1 to 7 in the preparation of tannic acid feed additives, characterized in that, The coating material is used to form a gastrointestinal coating on the surface of tannic acid particles to reduce the shell membrane residue after the coating disintegrates in the intestine.

Citation Information

Patent Citations

  • Preparation method and application of novel stomach and intestinal tract passing sustained-release tannic acid

    CN120345648A